Mycorrhizal colonization of mountain cypress seedlings in relation to phosphorus and water availability under nursery conditions - Massone, Diego S; Martucci, Analía A; Askenazi Vera, Julieta E; Pastorino, Mario J; Bartoli, Carlos (Bosque (Valdivia), 2023)
The association of roots with mycorrhizal fungi increases the establishment success of forest species. Cordilleran cypress naturally forms associations with arbuscular mycorrhizae (AM). In general, the use of fertigation and artificial growth methods causes a decrease in mycorrhization, which could lead to a decrease in seedling performance in the field. The objectives of this study were: to determine whether AM colonization occurs in a nursery; to evaluate the influence of differing availability of phosphorus and substrate water status on the level of mycorrhizal colonization during plant growth; and to analyze the abundance of mycorrhization and its relationship with post-planting survival. The trial treatments were only applied during plant growth and consisted of a combination of three phosphorus concentration levels (1, 10 and 100 mg L-1) and two substrate water statuses (20 and 80 % of the container capacity (Cc)). The percentage of mycorrhization (% AM) was evaluated in plants grown in a nursery, in a sterilized substrate in the field, as was its survival in the field. Among the most relevant results, 24 % AM was found in the nursery while this value increased in the field (93 %), indicating that the mycorrhizal colonization process occurs during plant growth, even though it is partially inhibited by phosphorus and water management. It was also observed that the % MA increased once the plant was taken to the field independently of the % MA of the seedling in the nursery.